Assessing the resistance of Brachiaria hybrids to pathogenic Rhizoctonia - Álvarez, E.; Latorre, M.; Bonilla, Ximena P.; Miles, John W. (Scientific Societies, 2014)
Rhizoctonia foliar blight, caused by Rhizoctonia solani anastomosis group 1, is an economically important fungal disease found throughout the world. The fungus attacks numerous crops, including cereals, roots and tubers, legumes, and cruciferous, horticultural, and ornamental plants. In tropical America, this invasive and destructive disease also attacks most Brachiaria spp. used as forages in the ranching industry, especially in the production of cattle. Research to solve this constraint has been ongoing at the International Center for Tropical Agriculture and has generated new Brachiaria hybrids with excellent agronomic performance, tolerance to poor soils, and, particularly, high resistance to biotic factors such as Rhizoctonia foliar blight. These hybrids belong to lines obtained from Brachiaria humidicola, B. brizantha, and B. decumbens. To identify resistance among Brachiaria hybrid genotypes, the hybrid clones were evaluated for their variability in resistance, and their disease reaction was also determined and characterized. Results led to the identification of hybrids that not only were highly resistant to the blight but also had excellent agronomic characteristics.